Money Politics As A Form Of Risywah: Perspective Of The 2012 Munas-Konbes Bahtsul Masail Of Nahdlatul Ulama - Putra Kurniawan; Fatmah (JURNAL ILMU SYARIAH, 2026)
The practice of money politics in village head elections remains a problem that threatens the quality of democracy and also raises debate from an Islamic legal perspective, as it bears similarities to the concept of risywah (bribery). This study aims to analyze the practice of money politics in village head elections in Indonesia and examine its position as a form of risywah based on the ruling issued by the Bahtsul Masail Diniyyah al-Waqi'iyyah commission at the 2012 Musyawarah Nasional (Munas) Alim Ulama and Konferensi Besar (Konbes) Nahdlatul Ulama, held 14–17 September 2012 at Pondok Pesantren Kempek, Cirebon. The study employs a normative legal research method, a conceptual approach, and an explicit literature-selection procedure. Data were obtained through a library study of Islamic legal literature, laws and regulations, the views of the ulama, and the published proceedings of the 2012 Munas-Konbes, and were then analyzed descriptively and analytically. The results, understood as a literature-derived typology rather than original field findings, indicate that money politics in village head elections is described in the literature through various forms of material gifts, such as money, personal assistance, and certain facilities aimed at influencing voter choices. The 2012 Munas-Konbes ruling, read together with subsequent scholarly analysis of its reasoning, emphasized that this practice falls into the category of risywah, prohibited when aimed at securing political support, while distinguishing this from giving intended to help a reform-minded candidate defeat a corrupt one, and addressing not only the giving candidate's liability but also the legal position of the receiving voter. This study concludes that money politics is a form of electoral corruption that not only damages local democracy but also violates sharia values, so that strengthening political education, religious awareness, and effective supervision are needed to prevent this practice. Keywords: Risywah; Money Politics; 2012 Munas-Konbes Bahtsul Masail; Nahdlatul Ulama.